(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Aim: Anemia is a condition where the amount of hemoglobin (Hb) in the blood is below the normal level, or there are fewer red blood cells (RBCs) than normal. Hematinics are substances that are essential to the proper formation of the components of blood. Materials and Methods: The leaves of Asparagus racemosus, Boerhavia diffusa, and Phyllanthus emblica were used for preparing herbal tea in the present study. The herbs were evaluated for physicochemical parameters, such as extractive values and ash content and phytochemical screening was also carried out. The formulated herbal tea bags were evaluated for physicochemical parameters, spectroscopic analysis, total phenolic, and total flavonoid content. Acute oral toxicity studies and pharmacological evaluation of herbal tea for hematinic activity (phenylhydrazine-induced anemia) was carried out in rats. Results and Discussion:The results revealed significant change in RBC, packed cell volume, and Hb in anemic rats. Conclusion: From this study, it is concluded that the herbal tea bag composed of A. racemosus, P. emblica, and B. diffusa possesses significant hematinic activity.